SURVEI POPULASI KAPANG DAN KADAR HCN PADA ONGGOK DENGAN PROSES PENGERINGAN YANG BERBEDA DI PROPINSI LAMPUNG - Fadlilah Ahmad Afrian; Liman .; Syahrio Tantalo (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This study aimed to compare the populations of fungi and HCN levels in cassava waste drying on thesoil and cement floors. Implementation of the research conducted at September-October. Cassavawaste sample have from East Lampung and Center Lampung. Populations of fungi analysis inLaboratory of Microbiology, Department of Biology, Faculty of Mathematics and Natural Sciences,Lampung University. HCN levels analysis in Laboratory and Nutrition, Department of AnimalHusbandry, Faculty of Agriculture, Lampung University. This study used a survey method. Thesampling technique using non-probability samples by purposive sampling. Data populations of fungiare transformed using log x, then data population of fungi and HCN levels were analyzed usingstudent's t-test at 5% significance level.Average populations of fungi in cassava waste drying on the ground is 113.71 103 cfu/gr and thecement floor is 77.60 103 cfu/gr. Average HCN levels in cassava waste drying on the ground is 94.31ppm and cement floor is 77.56 ppm. The results showed that the populations of fungi and HCN levelsin cassava waste with drying on the ground and the cement floor was non significant differences(P>0.05).